185k views
2 votes
F(x) = 2x^2 + 4x - 6g(x) = 4x^3 – 6x^2 + 3=Find (f + g)(x).

1 Answer

3 votes

Answer:


(f+g)(x)=4x^(3)-4x^(2)+4x-3

Explanations:

Given the following parameters


\begin{gathered} f(x)=2x^2+4x-6 \\ g(x)=4x^3-6x^2+3 \end{gathered}

Find the sum of the functions


\begin{gathered} (f+g)(x)=f(x)+g(x) \\ (f+g)(x)=2x^2+4x-6+(4x^3-6x^2+3) \end{gathered}

Expand the parenthesis


\begin{gathered} (f+g)(x)=2x^2+4x-6+4x^3-6x^2+3 \\ (f+g)(x)=4x^3+2x^2-6x^2+4x-6+3 \\ (f+g)(x)=4x^3-4x^2+4x-3 \end{gathered}

User Bob Whiteman
by
5.0k points